ANTIOXIDANT ACTIVITY AND FT-IR ANALYSIS OF DATURA INNOXIA AND DATURA METEL LEAF AND SEED METHANOLIC EXTRACTS - Bhardwaj, Khushboo; Kumar, Sanjiv; Ojha, Sudarshan (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Datura (family- Solanaceae), has a long history of being used as herbal medicine. These medicinal effects have been attributed to the phytochemicals present in the plant leaves and seeds, in particular alkaloids, flavonoids and phenolic compounds. The objective of this study was to investigate the methanolic leaf and seed extracts of Datura innoxia (DLP-I & DSP-I) and Datura metel (DLP-M & DSP-M) for their total phenolic, flavonoids and in-vitro antioxidant properties. Materials and Methods: Determination of total phenolic content and total flavonoid content and antioxidant activity in terms of total antioxidant assay, ABTS assay, DPPH assay and in-vitro lipid peroxidation inhibiting activity were determined along with the FT-IR (Fourier transform infrared spectroscopy) analysis of the extracts. Results: The highest total phenolic and total flavonoid content were registered by the D. innoxia leaf extract (70.26 ± 1.12 mg GAE/g and 34.24 ± 1.28 mg RE/g respectively). Maximum DPPH radical scavenging activity was exerted by the leaf extract of D. innoxia (IC50 = 146.69 ± 8.46 μg/mL) among the four different methanolic extracts. The highest activity of the ABTS assay was found in Datura innoxia leaf extract (IC50 value = 149.42 ± 13.43 μg/mL) and the highest total antioxidant capacity was found to be present in D. innoxia leaf extract (221.25 ± 1.06 mg AAE/g) whereas D. metel seed extract registered the maximum lipid peroxidation inhibition activity (IC50 = 112 ± 1.30 μg/mL). The FT-IR data also supported the maximum activity in D. innoxia (leaf and seed) extracts. Conclusion: The results thus obtained suggested that the plant Datura innoxia possess considerable antioxidant activity over Datura metel and therefore can be established as a potential source of natural antioxidant.